Plasma deposited amorphous tungsten nitride diffusion barrier for metal-organic chemical vapor deposited Cu metallization - Kim, Yong Tae; Lee, Chang Woo (Chinese Institute of Electrical Engineering, Taipei, Taiwan, 1995)
Copper thin films are deposited on amorphous tungsten nitride diffusion barriers by a metal-organic chemical vapor deposition method. The deposition rate and preferential orientation of (111) vs. (200) ratio of Cu film are considerably lower than those of Cu films deposited on SiO2, boro-phospho-silica glass, and Si due to substrate-driven reaction. RBS and XRD measurements clearly show that 100-800 angstrom amorphous W67N33 layer successfully executes the role of diffusion barrier for Cu during the annealing process at 800°C for 30 min.
Keywords: Amorphous materials; Annealing; Copper; Glass; Metallic films; Metallizing; Metallorganic chemical vapor deposition; Plasma applications; Rutherford backscattering spectroscopy; Silica; Thin films; X ray diffraction; Borophosphosilica glass; Diffusion barrier; Tungsten nitride; Tungsten compounds